Checagem automática de projetos em BIM utilizando programação visual: um estudo da Lei de uso e ocupação dos Solos de Crateús-CE - Alves, Rafaelly Beserra (2022)
BIM (Building Information Modeling) has been an important means of improving quality and productivity in the construction sector. Among its benefits, it’s interest of this research the possibility of automating work routines, as checking projects necessary for the granting of construction permits, optimizing valuable time and resources for companies and public authorities. However, this optimization requires objective laws, which can be translated into a programming language, which is not trivial. In this way, we sought to explore the following research question: how can the visual programming language for automatic checking of BIM projects be applied to the Land Use and Occupation Law (LUOS) of Crateús, CE? Therefore, the present work aimed to analyze the applicability of the visual programming language for automatic checking of BIM projects according to LUOS of Crateús, CE. Therefore, the research was developed following the Design Science Research methodology. As a result, the application process of the LUOS of Crateús was analyzed, based on the law and four interviews with professionals working in the region, including the city hall project analyst. It could be seen that the law is not effectively applied, and that not all items for approval are verified (or required in their entirety). Next, it was verified that approval criteria for residential projects by LUOS of Crateús can be automatically checked through BIM models, where the great potential for automating the law was verified, with most of the criteria class 2 in relation to their processing complexity, out of a total of 4 classes. With this analysis, an artifact was developed for automatic checking of rules for the law in question, through visual programming in Dynamo. The artifact consisted of 6 routines capable of checking the main urban indexes of LUOS de Crateús (use index, occupancy rate, tested, setbacks and template), as well as some observations of the law. It was verified how visual programming can be a great ally for the customization and optimization of project analysis routines. It was found that the level of detail was expected for legal projects, without the need for an extensive amount of information. Finally, the proposed LUOS automatic checking solution was applicable, since the developed artifact is a working instantiation. In addition, it is not only a viable artifact, since it correctly returns the necessary information, but it is necessary, since it is a way of guaranteeing the application of rules equally to individuals and ensuring the basic objective of this legislation, which is urban planning.